Analisis Pengaruh Gaya Hidup Hedonis Terhadap Perilaku Konsumtif Dalam Perspektif Ekonomi Islam Pada Masyarakat Desa Jero Gunung Kecamatan Sakra Barat Kabupaten Lombok Timur - Sholihah, Isfi; Riswanto, Agus; Zain, Rohaeniyah; Safitri, Yuliana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Consumption is the most basic human need. This is clearly  proven  in  the  people  of  Jero  Gunung  Village  where irrational and excessive consumption behaviour has been operating due to a hedonic lifestyle pattern. In fact, in Islamic economics, needs must be oriented towards rational and positive needs in accordance with the Islamic law. This research aims to determine the influence of a hedonic lifestyle on consumer behaviour from an Islamic economic perspective in the people of Jero Gunung Village. This type of research was quantitative correlational. The population of this research was the people of Jero Gunung Village who are indicated to have consumptive behaviour. The total research sample was 42 people using Simple Random Sampling techniques. The data analysis technique used in this research was simple regression analysis. The results of the research hypothesis test show that T count  >  T  table  with  scores  3.202  >  2.021.  Therefore,  the hypothesis which states "There was a significant influence between hedonic lifestyle and consumer behavior in the people of Jero Gunung Village" was accepted. The coefficient of determination or R2 shows a value of 0.204, which means that the hedonic lifestyle variable has an influence of 20.4% on the consumptive behaviour variable.   In   general,   the   hedonic   lifestyle   and   consumptive behaviour of the people of Jero Gunung Village are in the moderate category